Forests, wildlife, and economy: the role of hunting tourism in Czechia’s sustainable forest management - Markéta Kalábová; Radek Rinn; Milosava Matejević; Vladimir Marković; Tomáš Kušta; Radim Löwe; Dimitra Lazaridou (Frontiers in Forests and Global Change)
Forests and forest ecosystems are vital for providing habitats to wildlife while also supporting economic activities beneficial to society. Among these, hunting tourism represents a valuable economic opportunity across European regions, particularly in remote rural areas, and its integration into sustainable forest management can amplify the value of forest ecosystems. Integrating hunting tourism into sustainable forest management can enhance the long-term environmental, social, and economic value of forest ecosystems. The aim of this study is to assess the economic impact of hunting tourism as an integral part of sustainable forest management and restoration efforts in Czechia, with a particular focus on its contribution to the national economy between 2019 and 2022. Utilizing an input–output model and multiplier analysis, it quantifies both direct and indirect economic impacts based on domestic and foreign hunting tourist numbers, their expenditures, and symmetric input–output tables (SIOT), highlighting interdependencies among economic sectors. Results showed that hunting tourism contributes over 80 million euros annually to Czechia’s economy, though income saw a decline in 2020 and 2021 due to the Covid-19 pandemic. The findings emphasize the role of forest management in sustaining wildlife resources, alongside the importance of data-driven decision-making, enabling policymakers and stakeholders to develop growth strategies that support both economic resilience and ecological restoration.